Preliminary examinations of the International Criminal Court in Latin America: the Colombian case and its impact on future peace negotiations in the region - Olásolo Alonso, Héctor (Anuario de Derechos Humanos, 2014)
The article initially traces back the International Criminal Court Prosecutor’s role in the application of the complementarity principle in preliminary examinations during the first ten years of the International Criminal Court. The article emphasizes the role played by preliminary examinations in strengthening countries national jurisdictions and the rule of law, verifying that each case requires a different strategy due to its particular circumstances. Crimes against humanity characteristics in Colombia are subsequently analysed and the consequences of its configuration as a jus cogens international crimes. Based on the aforementioned, it discusses the impact of preliminary examinations on the current peace negotiations between the Colombian Government and the FARC developed by the International Criminal Court Prosecutor. In conclusion, the article gives some final observations about the importance of preliminary examinations for future peace negotiations in the region beyond the Colombian case.